2020
DOI: 10.1097/sap.0000000000002389
|View full text |Cite
|
Sign up to set email alerts
|

Applied Online Crowdsourcing in Plastic and Reconstructive Surgery

Abstract: Background Aesthetic outcomes of unilateral cleft lip repairs have important psychosocial implications for patients who are heavily influenced by social perceptions. Online crowdsourcing offers the unique potential to efficiently recruit large numbers of laypeople to assess public perception. The aim of this study was to use the online crowdsourcing platform Mechanical Turk to compare the postoperative outcomes of Fisher, Millard, and Mohler cleft lip repair techniques. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Forty-five articles were ultimately included for data extraction (Table 1). 13–57 Proportionate rater agreement was 91.7% for abstract screening and 92.5% for full-text screening. The Cohen kappa coefficient for interrater reliability was 0.82 for abstract screening and 0.81 for full-text screening, demonstrating sufficient interrater reliability.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-five articles were ultimately included for data extraction (Table 1). 13–57 Proportionate rater agreement was 91.7% for abstract screening and 92.5% for full-text screening. The Cohen kappa coefficient for interrater reliability was 0.82 for abstract screening and 0.81 for full-text screening, demonstrating sufficient interrater reliability.…”
Section: Resultsmentioning
confidence: 99%
“…Studies aiming to assess layperson opinion on surgical outcomes are commonly prone to recruitment difficulty and selection bias by geographic location or study pool [24,25]. As a result, the utilization of online crowdsourcing, specifically Amazon's Mechanical Turk (MTurk), in research has drastically increased as it offers the unique potential to efficiently recruit large numbers of layperson respondents to assess public perception [26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As a result, the utilization of online crowdsourcing, specifically Amazon's Mechanical Turk (MTurk), in research has drastically increased as it offers the unique potential to efficiently recruit large numbers of layperson respondents to assess public perception [26]. Furthermore, MTurk is specifically helpful in answering aesthetic questions such as "which size looks bigger" or "which belly button shape is nicer" as it offers a reduction in selection bias, ease of study design, and enhanced efficiency of large-scale participant recruitment [24]. This study aims to examine and quantify the aesthetic impacts of unilateral radiation on subsequent bilateral deep inferior epigastric perforator (DIEP) flap reconstruction by surveying both plastic survey experts and layperson volunteers through MTurk.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Platforms such as Amazon Mechanical Turk (MTurk), have previously investigated the concordance of layperson crowdsourced worker ratings with ratings of experts in the domains of cleft speech and Asher-McDade fixed-scale ratings, [8][9][10] and used MTurk to compare aesthetic outcomes in cleft lip repair. 11,12 Encouraged by the results of these studies, which found that online crowdsourced ratings are highly consistent with expert opinion, we aim to understand lay perspective of cleft outcomes using a novel technique of simulating different lip angles and scar thicknesses.…”
mentioning
confidence: 99%